Jake and Lily - Spinelli, Jerry (London: : Orchard Books, 2013)
Twins Jake and Lily have a very close relationship, but when they turn eleven, their parents give them separate bedrooms and Jake begins to spend time with a group of neighborhood boys. Lily is devastated as she struggles to make friends, and Jake is faced with a bully.
3.2
3-6.
3-6
Keywords: Brothers and sisters -- Juvenile fiction; Bullying -- Juvenile fiction; Friendship -- Juvenile fiction; Individuality -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Fiction; Bullies -- Fiction; Friendship -- Fiction; Individuality -- Fiction; Twins -- Fiction; Bullies -- Fiction; Friendship -- Fiction; Individuality -- Fiction; Siblings -- Fiction; Twins -- Fiction